Big Money: What It Is, How we Use It, and Why Our Choices Matter - Donnelly, Rebecca (New York : Henry Holt and Company, 2023)
"Big Money aims to explain economic principles to middle- grade readers in a way that combines the weird and the meaningful, like Planet Money for kids. The book will be organized in seven chapters, each posing a general question and answering it through real-world examples to help readers explore the consequences of their everyday economic choices by connecting the dots between themselves and the larger economic and social systems around them"--
Ages 8-12
Keywords: Economics -- Juvenile literature; Money -- Juvenile literature